Select of the most suitable simulation for design and management of the wastewater treatment system for the SaVan-XeNo industrial park.: https://doi.org/10.69692/SUJMRD0802266 - PHANTHAVONG, Vongphone; CHANSOMPHOU , Vatthanamysay; VONGKHAMSY, Hoummala (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
Now, water environment in industrial zones increasingly contaminated by wastewater. Therefore, the production facilities must build preliminary processing system before discharging into the collective wastewater treatment system. The study aims to provide an optimal scenario for installation design and operate the wastewater treatment system to effectively nutrients remove. In the case study, the scenarios are simulated by the ASM2d model (Activated Sludge Model No. 2d) based on the AAO (Anaerobic, Anoxic, Aerobic/Oxic) and SBR (Sequencing Batch Reactor) system to select scenarios that have met NH4+ ≤3 mg/l, TN ≤ 5 mg/L, TP ≤ 1 mg/L associated with American and Lao standards. The results showed 269/855 scenarios were satisfactory, 16 scenarios optimized in AAO system. and 27/180 scenarios of the SBR system have been achieved, 4 scenarios achieved optimization. In the study, the optimal simulation scenario of the AAO system was more suitable than the SBR system with a total volume of 2,056 m3 and oxygen consumed 509,364 kg/day.